STUDENT ACHIEVEMENTS AND THEIR ATTITUDES TOWARD COURSE DESIGN - A CORRELATION ANALYSIS - Gardašević, Dragana; Banjević, Koviljka; Nastasić, Aleksandra; Rošulj, Dragana (Journal of process management and new technologies, 2023)
Besides the distance learning has existed for a long time, for the great number of Higher Education Institutions it was the ‘’consequence’’ of Covid-19 pandemic. This was case of HE Sector in Serbia. In some earlier research, the authors of this paper considered students’ performance and their attitudes toward distance learning, separately. The main idea of this study is to investigate the correlation between student attitudes toward distance education and their achievements. The sample included students of The Academy of Applied Technical Studies Belgrade – Department of Belgrade Polytechnic, who attended different year of the same study programme. Students` achievements were measured through GPA and average efficiency within courses of the first, second and third years of study programme. In this research, two instruments were used – questionnaire and data related to students` scores. Research methods included descriptive statistics and correlation analysis. The obtained results could be useful for present and future research, improvements of educational process, instructors and stakeholders from this area.